Frailty phenotype and frailty index are associated with distinct neuromuscular electrophysiological characteristics in men. Issue 8 (27th May 2019) - Swiecicka, Agnieszka; Piasecki, Mathew; Stashuk, Daniel W.; Ireland, Alex; Jones, David A.; Rutter, Martin K.; McPhee, Jamie S.
Abstract : New Findings: What is the central question of this study? Human frailty is characterized by accumulated health complaints, including medical conditions, low physical and psychological function and social components. It is currently unknown whether the condition is associated with neuromuscular changes detectable by electrophysiology obtained from voluntary and involuntary muscle contractions. What is the main finding and its importance? A higher likelihood of frailty was significantly associated with a smaller size of vastus lateralis motor unit potentials during voluntary contractions and smaller compound muscle action potentials generated by electrical stimulation. Importantly, these associations were independent of age and body mass index. Abstract: The purpose of this study was to determine whether neuromuscular electrophysiological characteristics that are known to underlie sarcopenia are also associated with the more complex frailty syndrome. Eighty‐six men [mean (SD) age, 74 (8) years] were classed as non‐frail (robust), prefrail or frail using criteria from the frailty phenotype (FP) and the frailty index (FI). The femoral nerve was stimulated maximally and the resulting compound muscle action potential amplitude (CMAP) measured over the vastus lateralis. Motor unit potential (MUP) size was assessed during voluntary contractions using intramuscular electromyography (iEMG). Logistic and negative binomial regression models determined relationships between FP and FI with CMAP and MUP sizes before and after adjustments for age and body mass index. Larger CMAP size was associated with a lower likelihood of frailty in fully adjusted models: a 1SD higher level in vastus lateralis CMAP size was associated with a 0.4 (95% confidence interval: 0.2, 0.6; P  < 0.01) unit lower FI (40% of the FI range) and more than halving of the odds [odds ratio: 0.43 (95% confidence interval: 0.21, 0.90)] of having a frail/prefrail phenotype. Greater MUP size was also related to lower FI values using unadjusted and fully adjusted models. However, MUP size was not significantly related to FP in any model. Smaller MUPs and a smaller CMAP were significantly associated with a higher likelihood of frailty, independent of age and body mass index. These results relate neuromuscular electrophysiological characteristics to the complex frailty syndrome and identify motor unit remodelling as a possible contributing factor. Abstract :